Promosi Kesehatan dan Pendampingan Tentang Flouride Dalam Upaya Mencegah Terjadinya Karies Gigi Anak - Sallo, Andi Kamal M.; Asnur, Syamfitriani; Musaidah, Musaidah; Mardiah, Ainun; Nurhidayati, Lailiana Garna; Rejeki, Desi Sri (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Parents, especially mothers, have an important role in maintaining the health of their family members. The role of parents is very much needed in guiding, providing understanding, reminding, and providing facilities to children and their family members so that they can maintain their dental and oral hygiene. In efforts to care for teeth and mouth, the amount of information obtained by mothers will affect the efforts of the family's dental and oral health. Mothers will be better at teaching how to brush their teeth, arranging the correct snack patterns and various other efforts in maintaining the dental and oral hygiene of their family members, so that knowledge about dental and oral health will be better. The purpose of community service activities is that promotion about fluoride will increase mothers' knowledge in efforts to prevent dental caries and improve the level of dental and oral health in children. The service method with Health Promotion and Guidance About Fluoride in Efforts to Prevent Dental Caries in Children about fluoride as a promotional media to increase mothers' understanding of fluoride knowledge. The results of the Community Service activities are that knowledge about fluoride and the skills of how to brush teeth properly and correctly owned by mothers, improve the dental and oral health of their family members so that it will prevent the risk of dental caries, especially in their children. The conclusion of this activity is that there is an effort to prevent tooth decay by guiding children to always maintain the cleanliness of their teeth and mouth by brushing their teeth properly, correctly and regularly and using toothpaste containing fluoride.